2005
DOI: 10.1051/parasite/2005124353
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the efficacy of specific treatment in chronic Chagas disease by polymerase chain reaction and flow cytometry analysis

Abstract: Summary :PCR and FC-ALTA were used to monitor parasite clearance in 54 chronic chagasic patients who had completed therapy with allopurinol (ALLO, n = 31) or itraconazole (ITRA, n = 23) ten years earlier. All patients maintained positive conventional serology. 25 of them showed positive XD (ALLO, n = 11 and ITRA, n = 14) and 29 negative XD (ALLO, n = 20 and ITRA, n = 9). 43 patients were positive by both techniques (ALLO, n = 23 and ITRA, n = 20). Seven of 54 patients were negative by PCR and positive by FC-AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…PCR has been introduced to detect T. cruzi in blood samples from Chagas patients (Moser et al 1989, Sturm et al 1989, Avila et al 1991, Britto et al 1993, Wincker et al 1994, Kirchhoff et al 1996, Gomes et al 1998, Castro et al 2002 and also used to monitor treatment outcomes in both the acute and chronic phases of Chagas disease (Britto et al 1995, Russomando et al 1998, Solari et al 2001, Galvão et al 2003, Schijman et al 2003, Zulantay et al 2004, Sanchez et al 2005. These studies confirmed the usefulness of PCR strategies as a clinical tool for early detection of treatment failure.…”
Section: What Remains To Be Done With Regard To Follow-up Studies?supporting
confidence: 55%
“…PCR has been introduced to detect T. cruzi in blood samples from Chagas patients (Moser et al 1989, Sturm et al 1989, Avila et al 1991, Britto et al 1993, Wincker et al 1994, Kirchhoff et al 1996, Gomes et al 1998, Castro et al 2002 and also used to monitor treatment outcomes in both the acute and chronic phases of Chagas disease (Britto et al 1995, Russomando et al 1998, Solari et al 2001, Galvão et al 2003, Schijman et al 2003, Zulantay et al 2004, Sanchez et al 2005. These studies confirmed the usefulness of PCR strategies as a clinical tool for early detection of treatment failure.…”
Section: What Remains To Be Done With Regard To Follow-up Studies?supporting
confidence: 55%
“…Several studies have demonstrated the usefulness of this test to assess the therapeutic response and the treatment efficacy because it exhibits greater sensitivity than other parasitological tests, especially during acute cases and congenital infection or reactivation. Molecular tests, unlike serological tests, allow the short-term detection of treatment failure [26,3436]. Real-time PCR (qPCR) allows for the quantification of the parasite load in samples from patients with T. cruzi infection, and this test has been proposed as a marker of therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes, passage through the cell cycle is governed by the function of a family of protein kinase complexes (18). Under normal conditions, the protein kinase complexes are activated at specific intervals and through a series of events, resulting in the progression of cells through the different phases of the cell cycle, thereby ensuring normal cell growth (19). Any defect in this machinery causes altered cell cycle regulation that may result in unwanted cellular proliferation, potentially culminating in the development of cancer.…”
Section: Discussionmentioning
confidence: 99%